64.9k views
5 votes
Can you solve (4k-9)(2k-2 in algebra 1 put it in explanation​ on how you got your answer

User TravisG
by
5.2k points

1 Answer

2 votes

(4k-9)(2k-2)

First you're going to want to multiply the 4k by the 2k & the -2. Then you're going to want to multiply the -9 by the 2k and the -2.

(4k-9)(2k-2)

4k * 2k = 8k^2

4k * -2 = -8k

-9 * 2k = -18k

-9 * -2 = +18

Since we have like terms (-8k and -18k) put those together.

-8k + -18k = -26k.

Now you're going to want to put all of these together in an equation.

You want to order the numbers from the highest number of exponents (8k^2) to the lowest.

8k^2 - 26k + 18

So the correct answer is 8k^2 - 26k + 18.

User Wildroid
by
6.3k points